Trend of depression and its association with sociodemographic and clinical factors among multiple myeloma hospitalizations - a Portuguese nationwide study from 2000 to 2015 - Francisco Ribeiro de Carvalho (2020)
Objective: Patients hospitalized with multiple myeloma (MM) are particularly vulnerable to depression. The present study aims to determine the frequency of depression among MM hospitalized patients, in order to assess the possible differences between those with and without depression in relation to sociodemographic and clinical variables and to measure the impact of depression on hospitalization outcomes. Methods: An observational retrospective study was performed using an administrative data set of all hospitalizations with a primary diagnosis of MM between 2000 and 2015 in Portuguese mainland public hospitals. Codes related to depressive disorders were grouped to generate the dichotomous variable of depression (yes/no). A multivariate analysis was conducted and adjusted odd ratios (aOR) calculated between different variables and depression. Results: Of a total of 14,575 MM hospitalizations studied, a concurrent code of depression was registered in 666 patients (4.6%). A greater odds of depression was observed in female patients (aOR= 2.26; 95%CI=1.91-2.66), transplanted patients (aOR= 1.78; 95%CI=1.44‐2.20), patients with plasma cell leukemia (aOR= 1.79; 95%CI=1.22‐2.64) and patients with a higher Charlson Comorbidity Index (CCI) (aOR= 1.10; 95%CI=1.05‐1.15). Length of stay was longer in patients with a registered diagnosis of depression (aOR= 1.01; 95%CI=1.01‐1.02) while the odds of in-hospital mortality were lower in these patients (aOR= 0.53; 95%CI=0.41-0.68). Conclusions: These results may help identify MM inpatients at higher risk of presenting depression (female gender, younger age, high CCI, plasma cell leukemia, transplant procedure). This will enable timely psychological assessment and treatment in order to prevent worse outcomes and higher healthcare costs associated with depression.